STRATEGI PEMASARAN KERIPIK TERONG PADA USAHA HOME INDUSTRI KRIPIK TERONG YANG ADA DI DESA SRIWANGGI SEMENDAWAI SUKU III OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
The marketing of eggplant chips that have been carried out is from producers to consumers and producers to middlemen and then to consumers. This is what underlies the researcher to examine the marketing strategy of eggplant chips in the eggplant chip home industry business in Sriwanggi Semendawai Village, Tribe III East OKU. The purpose of this study was to find out what factors make eggplant chips products favored by consumers and to analyze marketing strategies for eggplant chips home industries to increase sales in East OKU Regency. Based on the results of the study, the factors that influence consumer demand for eggplant chips in Sriwangi Village, Semendawai District, Tribe III are price, product accessibility, lifestyle and type of work, showing a significant influence on eggplant chips demand. While the variables of taste, packaging and gender have a significant effect on the purchase of eggplant chips. The Marketing Strategy that has been carried out by the Eggplant Chips Home Industry is an aggressive strategy with more focus on the S-O (Strength-Oppertunity) strategy, namely by using strengths to take advantage of existing opportunities. The SO (Strength-Oppertunity) strategy is: a. Maintaining price and quality to maintain customer loyalty. b. Continue to innovate and develop products, tastes and services to slow down the pace of positioning in the market